BODIPY‐Based Photodynamic Agents for Exclusively Generating Superoxide Radical over Singlet Oxygen - Teng, Kun‐Xu; Chen, Wen‐Kai; Niu, Li‐Ya; Fang, Wei‐Hai; Cui, Ganglong; Yang, Qing‐Zheng (Angewandte Chemie International Edition, 2021)
Developing Type‐I photosensitizers is considered as an efficient approach to overcome the deficiency of traditional photodynamic therapy (PDT) for hypoxic tumors. However, it remains a challenge to design photosensitizers for generating reactive oxygen species by the Type‐I process. Herein, we report a series of α,β‐linked BODIPY dimers and a trimer that exclusively generate superoxide radical (O2−.) by the Type‐I process upon light irradiation. The triplet formation originates from an effective excited‐state relaxation from the initially populated singlet (S1) to triplet (T1) states via an intermediate triplet (T2) state. The low reduction potential and ultralong lifetime of the T1 state facilitate the efficient generation of O2−. by inter‐molecular charge transfer to molecular oxygen. The energy gap of T1‐S0 is smaller than that between 3O2 and 1O2 thereby precluding the generation of singlet oxygen by the Type‐II process. The trimer exhibits superior PDT performance under the hypoxic environment. Heavy‐atom‐free boron dipyrromethene (BODIPY)‐based photosensitizers generate ROS exclusively by the Type‐I process upon near‐infrared light illumination for tumor ablation.